RELATIONSHIP BETWEEN BCG VACCINATION HISTORY AND THE INCIDENCE OF LEPROSY IN CHILDREN: A LITERATURE REVIEW: Hubungan Antara Riwayat Vaksin BCG dan Kejadian Kusta Pada Anak: Sebuah Tinjauan Literatur - Noer Auliyah Madani Pertiwi, Aisyah; Martini, Santi; Mohamed Gomaa Nasr, Nayla (Jurnal Berkala Epidemiologi, 2024)
Background: Globally, 9,052 new cases of leprosy in children were reported, with a corresponding rate of 4.5 per million child population. Children are believed to be the most vulnerable group to M. leprae infections due to their immature immunity. Purpose: This study aims to determine the relationship between the history of BCG vaccination and leprosy incidence in children. Methods: This study used a literature review method that involved a systematic search. The data sources were obtained using several databases, namely Google Scholar, Proquest, Science Direct, and Pubmed. Keywords were built using the PICOS protocol and Boolean Operators, so the keywords used were "relationship" AND "BCG vaccine" AND "leprosy" AND "children". The research selection and search procedures were explained using the PRISMA 2020 method and research included in this study following the inclusion and exclusion criteria that have been set. Results: There were eight studies suitable for inclusion in this literature review. Five articles concluded that there was a relationship between the history of BCG vaccine and the incidence of leprosy in children, while three articles concluded that there was no relationship between the two variables. Conclusion: The BCG vaccine is useful as an effort to prevent the transmission and spread of leprosy in children. Children who do not receive BCG immunization are more susceptible to leprosy than those who receive immunization. The BCG vaccine has a protective effect to prevent children from contracting and transmitting leprosy to other people.